Exchange Rate Volatility And Macroeconomic Fundamentals In Four ASEAN Countries - Chong, Lee Lee (2006)

(untitled)
This study delineates the exchange rate volatilities of four ASEAN economies, namely Malaysia, Indonesia, Thailand and Singapore from four main aspects such as the movement of exchange rate and its macroeconomic factors, the regime-specific fundamental volatility and the impact of exchange rate volatility on economic fundamentals over the 1980-2004 period. This study aims to explore the exchange rate volatilities of these economies in providing a credible understanding of the behaviour of exchange rate volatilities and macroeconomic fundamentals. Exchange rate volatility is the risk occurred due to an excessive movement of exchange rate and many measures have been employed in the literature in estimating it. In this study, the exchange rate volatility is computed based on the exponential-GARCH specification, an extension of the widely-used GARCH model. The empirical results indicate that the Indonesian rupiah exhibited the highest volatility while the Singapore dollar fluctuated with the least. In between these two currencies are the Thai baht and Malaysian ringgit which were the second most volatile and second least volatile respectively.Exchange rate stability will benefit both policy makers and businesses. In view of the importance of exchange rate stability, this study examines the second aspect of exchange rate volatility to understand its macroeconomic factors. The results reveal that exchange rate volatility and relative macro variables are linked in both short- and long run although the short-run results seem to suggest that the influences of macroeconomic factors on the exchange rate volatility might differ given the different degrees of economic condition as well as financial and trade reforms. The result suggests that the significant common set factor is generated by stock market. The other aspect is to examine the macroeconomic shocks across alternative exchange rate arrangements for Malaysia, Indonesia and Thailand - three countries that have experienced shifts in their exchange rate arrangements since the 1970s. Singapore has had a rather consistent system. The empirical findings suggest that a majority of the examined variables behave differently across alternative exchange rate arrangements. The F-statistic results of virtual, traditional and augmented traditional fundamentals are also significant with the exclusion of Thailand’s traditional fundamental. Therefore, the exchange rate system is still a matter for the macroeconomic shocks for developing countries irrelevance of its trivial role in developed countries. Finally, this study offers an analysis of the impact of exchange rate volatility on international trade, international capital movement and economic growth as regards the four economies. A long-run relationship is detected although no relationship is found in the short run with the exception of Indonesia. This might suggest that most of the derivative products are more applicable for effective use in the short run rather than over a longer period.